Belzutifan for the treatment of renal cell carcinoma - Xiancheng Wu; David Lazris; Risa Wong; Scott S. Tykodi (Therapeutic Advances in Medical Oncology)
Belzutifan received its first FDA approval in 2021 for treating clinical manifestations of von Hippel-Lindau (VHL) disease including renal cell carcinoma (RCC) followed by approval in 2023 for treating advanced sporadic RCC that has progressed through multiple lines of treatment. It is the first FDA-approved drug to target hypoxia-inducible factor 2 alpha (HIF-2α). By inhibiting the HIF-2α transcription factor, belzutifan prevents HIF-2α from dimerizing with HIF-1β, thereby preventing the transcription of downstream oncogenes. Most clear cell renal cell carcinoma (ccRCC) tumors are associated with VHL deletion or inactivation resulting in HIF-2α overexpression that represents a key contributor to tumorigenesis, thereby making belzutifan a uniquely optimal drug for targeting ccRCC. Belzutifan has demonstrated activity in clinical trials as a front- and later-line therapy, and in combination with tyrosine kinase inhibitors. It has been largely well tolerated, although anemia represents a common on-target side effect and, along with hypoxia, requires monitoring during treatment. Ongoing phase III trials are investigating belzutifan in combination regimens in the relapsed/refractory, front-line, and adjuvant settings. Future studies will focus on identifying predictive biomarkers and resistance pathways.